Open-Book Management and Organizational Success of Deposit Money Banks in South-South, Nigeria (International Journal of Scientific Research and Management (IJSRM), 2021)
Organizational success is of the main drivers in achieving organizational goal and objectives as indicated in literature. Based on this evidenced the study focused the relationship between open book management and organizational success of deposit money banks in Nigeria. The study adopted quasi-experimental research design and examined the population of 200 employees with a sample size of 133 respondents in four deposit money banks in Nigeria. Questionnaire was the measure instrument for data collection and the collected data were analyzed using Spearman’s’ Rank Order Correlation Coefficient statistic. The result shows a significant relationship between the dimensions of open book management and organizational success measures of deposit money banks in Nigeria. Therefore, the study concluded that open book management affect organizational success and recommended that management should periodically make employees to know about the financial statues of the organization and to develop employees’ recognition programs and provide pay-performance programs that will stimulate employees’ performance toward achievement of organizational success.